EFFECT OF BOOM HEIGHT ON SPRAYING SWATH WIDTH OF JNKVV PUSH TYPE SOLAR AND BATTERY OPERATED SPRAYER - ATUL KUMAR SHRIVASTAVA; ALLURI PRAVEEN (The Bioscan, 2021)
The experiment was conducted to evaluate and measure the swath widths and spray angle produced by a spray boom held at four different heights above the ground whilst spraying with JNKVV push type solar and battery operated sprayer. JNKVV push type solar and battery operated sprayer is used to spray a chemical over a large area that helps in the growth of crops, reduce the expenditure on manual labour and are less time-consuming as compared with knapsack sprayer. The sprayer boom can be used for more than 50 cm row spaced crops and height adjustable boom for requirement of crop height. The swath width and spray angle of the sprayer during an application plays a critical role for chemical application. The sprayer boom was tested at different heights i.e. 40 cm, 80 cm, 120 cm, 160 cm from the ground level and found that the average swath width .i.e. 48.85 cm, 61.3 cm, 101.5 cm, 152.57 cm; average spray angle(degree) .i.e. 62.800, 41.920, 45.860, 50.980 respectively. It was analyzed that the height of spraying is directly proportional to the swath width. The spray angles of nozzles, pressure of spraying, height of spraying are responsible in enhancing the swath width. Coefficient of variation of average swath width at respective height were found to be 1.50 to 3.39, it means less variation in swath width at different heights.